Hubungan Tingkat Stres dengan Kualitas Tidur Mahasiswa Keperawatan dalam Mengerjakan Tugas Akhir - Larasati, Leony; Haro, Masta (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to analyze the relationship between stress levels and sleep quality in Nursing students of Universitas Advent Indonesia who are working on their final assignments. The method used is a cross-sectional design on 56 students of the 2022 intake who were selected by purposive sampling. The results showed that 41.1% of students experienced severe stress, 26.8% moderate stress, and 32.1% mild stress, while 60.7% had poor sleep quality. The Pearson correlation test showed a significant relationship between stress levels and sleep quality (p <0.05). This study concludes that the higher the stress level, the worse the sleep quality of students, which indicates a significant relationship between stress and sleep quality. Keywords: Sleep Quality, Thesis, Stress